Government 4.0 in Waste: Building a Clean Tech Ecosystem for a Sustainable Future - Dety Yunita Sulanjari; Djohar (Jurnal Penelitian Pendidikan IPA, 2025)
This study evaluates the increase in waste in the city of Makassar. Makassar, as the economic heart and urban center of eastern Indonesia, faces an unavoidable reality: a massive increase in waste volume. Every day, thousands of tons of waste are generated from households, markets, offices, and shopping centers. This is a direct consequence of rapid population growth, urbanization, and changes in the consumerist lifestyles of its residents. In the past, waste was dominated by easily biodegradable organic materials. However, today, the waste pile is dominated by single-use plastics, food and beverage packaging, and various other inorganic waste that takes hundreds of years to decompose in nature. This study used mixed methods, using quantitative methods to calculate waste generation and understand public perceptions, and qualitative methods to analyze the condition of natural objects. The results highlight the important role of local governments in reducing the potential for waste pollution and raising public awareness. Strict implementation of waste management policies, the provision of dedicated waste bins, and ongoing educational campaigns are needed. Outreach, training, and collaboration with the private sector and NGOs can ensure proper waste management, thereby reducing the potential for environmental pollution and protecting public health.